Pazopanib in the management of advanced soft tissue sarcomas - Cranmer LD; Loggers ET; Pollack SM (Dove Medical Press, 2016)
Lee D Cranmer,1 Elizabeth T Loggers,2 Seth M Pollack2 1Division of Medical Oncology, University of Washington, Seattle, WA, USA; 2Clinical Research Division, Fred Hutchinson Cancer Research Center, Seattle, WA, USA Abstract: Therapy of soft tissue sarcomas represents an area of significant unmet need in oncology. Angiogenesis has been explored as a potential target both preclinically and clinically, with suggestions of activity. Pazopanib is a multitargeted tyrosine kinase inhibitor with prominent antiangiogenic effects. In a Phase II study, pazopanib demonstrated activity in strata enrolling patients with leiomyosarcomas, synovial sarcomas, or other sarcomas but not those enrolling adipocytic sarcomas. PALETTE, the pivotal Phase III trial, demonstrated improved progression-free survival versus placebo in pazopanib-treated patients previously treated for advanced soft tissue sarcomas. No survival benefit was observed, and adipocytic sarcomas were excluded. Health-related quality-of-life assessments indicated significant decrements in several areas affected by pazopanib toxicities, but no global deterioration. Cost-effectiveness analyses indicate that pazopanib therapy may or may not be cost-effective in different geographic settings. Pazopanib provides important proof-of-concept for antiangiogenic therapy in soft tissue sarcomas. Its use can be improved by further biological studies of its activity profile in sarcomas, studies of biological rational combinations, and clinicopathologic/biological correlative studies of activity to allow better drug targeting. Keywords: pazopanib, soft tissue sarcoma, cost-effectiveness, PALETTE, angiogenesis, tyrosine kinase inhibitor